Battery

By controlling the content of nickel elements in lithium-ion batteries and the ratio of nickel-based positive electrode materials, combined with the relationship between H+ growth rate, the serious gas production problems caused by LMFP materials in lithium-ion batteries are solved, and the internal resistance of the battery is reduced and the circulation performance is improved.

CN119601590AActive Publication Date: 2025-03-11CALB GROUP CO LTD

Patent Information

Application Number
CN202411888964.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-11
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The high specific surface area of ​​the lithium manganese iron phosphate LMFP material in lithium-ion batteries leads to serious protonation of the electrolyte hydrogen, causing serious gas production problems and affecting battery performance.

Method used

By controlling the total molar amount of trivalent nickel and tetravalent nickel elements in lithium-ion batteries to the percentage of the total molar amount of nickel elements in nickel-based positive electrode materials, the molar ratio of nickel-based positive electrode materials to the active material of the positive electrode sheet, a specific relationship is met to reduce the battery gas production.

Benefits of technology

It significantly reduces the air production of the battery, ensures close contact between the battery pole plate and the diaphragm, reduces the internal resistance of the battery, and improves the circulating performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a battery. By controlling the percentage of the total molar amount of trivalent nickel elements and tetravalent nickel elements in the lithium ion battery to the total molar amount of nickel elements in the nickel-based positive electrode material, the molar ratio of the nickel-based positive electrode material to the positive electrode active material and the H < + > growth rate of the positive electrode plate, the gas production rate of the battery can be remarkably reduced; the close contact between the battery pole piece and the diaphragm is ensured, so that the internal resistance of the battery is reduced, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention with a filing date of October 30, 2024, an invention name of “A Battery” and an application number of 202411525404.2. Technical Field

[0002] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a battery. Background Art

[0003] Lithium manganese iron phosphate LMFP material is composed of manganese (Mn), iron (Fe), phosphorus (P) and lithium (Li) elements. As a positive electrode material for lithium batteries, lithium manganese iron phosphate LMFP has become a highly regarded material in new energy vehicles and energy storage systems due to its advantages such as high performance, stability and economy.

[0004] However, the LMFP material has a large specific surface area and a large contact area with the electrolyte, which will aggravate the protonation of hydrogen in the electrolyte. The protonated hydrogen is reduced at the negative electrode to produce hydrogen, resulting in serious gas production. Gas production will cause the pole piece to swell, the contact between the pole piece and the diaphragm to be loose, the impedance to increase, and black spots to appear on the pole piece.

[0005] Therefore, providing a lithium ion battery that can reduce gas generation becomes a problem to be solved. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a battery. The battery provided by the present invention can significantly reduce the gas production, ensure close contact between the battery pole piece and the diaphragm, thereby reducing the internal resistance of the battery and improving the cycle performance of the battery.

[0007] The present invention provides a battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material, wherein the positive electrode active material comprises a lithium manganese iron phosphate material and a nickel-based positive electrode material, wherein the nickel-based positive electrode material comprises a trivalent nickel element and a tetravalent nickel element, wherein the molar ratio of the nickel-based positive electrode material to the positive electrode active material is c; when the battery is in a state of 100% SOC, the total molar amount of the trivalent nickel element and the tetravalent nickel element to the total molar amount of the nickel element in the nickel-based positive electrode material is a; the H of the positive electrode sheet + The growth rate is b, and a, c and b satisfy the relationship shown in Formula I:

[0008] 0.008<(a×c) / b≤8.290, formula I.

[0009] Compared with the prior art, the present invention controls the percentage of the total molar amount of trivalent nickel and tetravalent nickel in the lithium-ion battery to the total molar amount of nickel in the nickel-based positive electrode material, the molar ratio of the nickel-based positive electrode material to the positive electrode active material, and the H +The growth rate can significantly reduce the gas production of the battery, ensure close contact between the battery pole piece and the diaphragm, thereby reducing the internal resistance of the battery and improving the cycle performance of the battery. DETAILED DESCRIPTION

[0010] The present invention provides a battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material, wherein the positive electrode active material comprises a lithium manganese iron phosphate material and a nickel-based positive electrode material, wherein the molar ratio of the nickel-based positive electrode material to the positive electrode active material is c; when the battery is in a state of 100% SOC, the nickel-based positive electrode material comprises a trivalent nickel element and a tetravalent nickel element, wherein the total molar amount of the trivalent nickel element and the tetravalent nickel element accounts for a percentage of the total molar amount of the nickel element in the nickel-based positive electrode material, and the H of the positive electrode sheet is + The growth rate is b, and a, c and b satisfy the relationship shown in Formula I:

[0011] 0.008<(a×c) / b≤8.290, formula I.

[0012] In the present invention, when a, b and c satisfy the relationship shown in formula I, the gas generation and expansion problems of the battery are significantly improved, and there is no black spot problem. Among them, the battery gas generation problem is comprehensively related to the values ​​of a, b and c, H + The larger the ion growth rate, the larger b is, the more serious the gas production is. At this time, an appropriate amount of high-valent Ni ions (a) are introduced. The catalytic oxidation activity of Ni ions is stronger than that of Mn ions, which can further oxidize proton hydrogen to produce absorbable gases such as CO and CO2, change the gas production path, and reduce the production of hydrogen.

[0013] When the calculated value of (a×c) / b exceeds the upper limit of the relationship, that is, exceeds the maximum value, it may be that the content of tetravalent and trivalent nickel elements is too much, which will affect the capacity of the battery and reduce the capacity of the battery. It may also be that H + The growth rate b is too small. A small b value means that the active area of ​​the positive electrode surface is small, resulting in a large lithium ion diffusion impedance and poor battery kinetics. When it exceeds the lower limit of the relationship, that is, exceeds the minimum value, it may be that H + The ion growth rate is too large, and the active area of ​​the positive electrode is large, resulting in severe dissolution of transition metal ions and damage to SEI, which leads to poor kinetics, increased DCR, and worsened cycle. It may also be that the content of trivalent nickel and tetravalent nickel in the positive electrode material is low in the entire positive electrode active material and cannot play a role in changing the gas production path. The hydrogen output is too large, affecting battery safety.

[0014] Therefore, the present invention can significantly reduce the gas production of the battery by controlling the values ​​of a, b and c to meet the range of 0.008<(a×c) / b≤8.290, ensure close contact between the battery pole piece and the diaphragm, thereby reducing the internal resistance of the battery and improving the cycle performance of the battery. In the present invention, (a×c) / b can be 0.009, 0.010, 0.02, 0.025, 0.03, 0.05, 0.1, 0.3, 0.5, 0.7, 0.9, 1.0, 1.5, 2.0, 2.5, 2.86, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.290, or any value between 0.008 and 8.290.

[0015] The structural formula of lithium manganese iron phosphate in the present invention is LiMn x Fe y M z n PO4, wherein M is a doping metal element, 0<x<1, 0<y<1, 0≤z<1, and 2(x+y)+n×z=2, n is the valence state of the doping metal element M, and the doping element M is selected from at least one of Be, Ca, Mg, Ba and Sr. The lithium manganese iron phosphate material used in the embodiment of the present invention is LiMn 0.6 Fe 0.4 PO4 is taken as an example, but it is not limited to this type of lithium manganese iron phosphate material.

[0016] As a preferred embodiment of the present invention, the total molar amount of trivalent nickel element and tetravalent nickel element accounts for the percentage of the total molar amount of nickel element in the nickel-based positive electrode material, the molar ratio of the nickel-based positive electrode material to the positive electrode active material, and the H + The growth rate satisfies the following relationship:

[0017] 0.025≤(a×c) / b≤2.860

[0018] In the present invention, the positive electrode active material includes lithium iron manganese phosphate material and a nickel-based positive electrode material. When the battery is in a fully charged state with a SOC of 100%, the nickel-based positive electrode material includes trivalent nickel elements and tetravalent nickel elements, and the total molar amount of the trivalent nickel elements and the tetravalent nickel elements accounts for a percentage of the total molar amount of the nickel element in the nickel-based positive electrode material, wherein the larger the a value, the greater the percentage of the total molar amount of the trivalent nickel elements and the tetravalent nickel elements in the total molar amount of the nickel element in the nickel-based positive electrode material; the smaller the a value, the smaller the percentage of the total molar amount of the trivalent nickel elements and the tetravalent nickel elements in the total molar amount of the nickel element in the nickel-based positive electrode material.

[0019] Compared with other valence states of nickel, trivalent nickel and tetravalent nickel have higher catalytic oxidation activity and are more easily reduced. The catalytic oxidation activity of trivalent nickel and tetravalent nickel ions is stronger than that of Mn ions, which can further oxidize proton hydrogen to produce CO, CO2 and other gases that can be absorbed by the electrode, changing the gas production path, thereby reducing the production of hydrogen. The value of a is related to the amount of lithium nickel oxygen positive electrode material LNO and nickel-containing ternary positive electrode material added. When the value of a is too high, the cost of battery preparation becomes high; when the value of a is too low, the effect of changing the gas production path cannot be achieved.

[0020] In the present invention, 0.3%≤a≤23%, can be 0.3%, 0.5%, 0.7%, 1%, 3%, 5%, 7%, 9%, 10%, 12%, 14%, 15%, 17%, 19%, 20%, 21%, 23%, or any value between 0.3% and 23%. In some preferred embodiments of the present invention, 1%≤a≤20%.

[0021] Therefore, the present invention can ensure that the gas production path of the battery is changed under the condition of low-cost battery preparation by controlling the range of the a value to be 0.3%≤a≤23%.

[0022] The test method of a is not limited in the present invention. Those skilled in the art can detect the percentage of the total molar amount of trivalent nickel element and tetravalent nickel element in the total molar amount of nickel element in the nickel-based positive electrode material according to conventional technical means. Exemplarily, the test method of a includes the following steps:

[0023] When the battery is fully charged at 100% SOC, the positive electrode is cleaned and the peak area of ​​each valence state of nickel in the positive electrode is tested by XPS. a is calculated according to the formula shown in formula II:

[0024] a=(S Ni 4+ +S Ni 3+ ) / S 总面积 Formula II;

[0025] In formula II, S Ni 4+ represents the area of ​​tetravalent nickel obtained by XPS test;

[0026] S Ni 3+ represents the area of ​​trivalent nickel obtained by XPS test;

[0027] S 总面积 It indicates the sum of the peak areas of each valence state of nickel element obtained by XPS test.

[0028] Specifically, the test method includes the following steps:

[0029] The positive electrode sheet was disassembled when the battery was in a fully charged state of 100% SOC, and was cleaned with DMC (dimethyl carbonate) and then dried to obtain a processed positive electrode sheet.

[0030] The present invention has no particular limitation on the drying method, and any drying method known to those skilled in the art may be used. In the present invention, vacuum drying is preferably used, the drying temperature is preferably 25° C., and the drying time is preferably 24 hours.

[0031] After obtaining the treated positive electrode sheet, it was etched by X-ray photoelectron spectroscopy (XPS) method with an etching rate of 0.7 nm / s and an etching time of 60 s. The peak area of ​​each valence state was fitted according to the binding energy. The sum of the peak areas of trivalent nickel element and tetravalent nickel element and the total peak area of ​​nickel elements of all valence states obtained by testing were calculated according to the formula shown in Formula II to obtain the value of a in %.

[0032] In some preferred embodiments of the present invention, the molar ratio of trivalent nickel element to tetravalent nickel element is 1:10-6:10, which can be 1:10, 1.5:10, 2:10, 2.5:10, 3:10, 3.5:10, 4:10, 4.5:10, 5:10, 5.5:10, 6:10, or any value between 1:10-6:10. If the molar ratio of trivalent nickel element to tetravalent nickel element is too large, it means that the content of trivalent nickel element is too much, and the effect of changing the gas production path is poor, and the output of hydrogen cannot be reduced; if the ratio is too small, it means that the content of trivalent nickel element is too little, and the battery life is significantly reduced; when the molar ratio of trivalent nickel element to tetravalent nickel element is within the range of 1:10-6:10, it can not only effectively change the gas production path of the gas, but also reduce the generation of hydrogen, while maintaining the battery life, so as not to reduce the battery life too fast.

[0033] In the present invention, the nickel-based positive electrode material is selected from one or more of lithium nickel oxygen positive electrode materials or nickel-containing ternary positive electrode materials.

[0034] In some specific embodiments of the present invention, the nickel-containing ternary positive electrode material is selected from a nickel-cobalt-manganese ternary positive electrode material, and the nickel-cobalt-manganese ternary material is LiNi x Co y Mn 1-x-y O2, wherein 0.9<x<1, 0<y<0.1, and x+y≠1.

[0035] In the present invention, there is no special restriction on the source of the lithium nickel oxygen positive electrode material or the nickel-containing ternary positive electrode material, which can be a commercially available product or can be prepared by a method known to those skilled in the art.

[0036] In the present invention, the preparation method of the lithium nickel oxygen positive electrode material is not limited, and those skilled in the art can prepare the positive electrode active material according to conventional technical means. Exemplarily, the preparation method of the lithium nickel oxygen positive electrode material includes the following steps:

[0037] First, the lithium source and nickel source required for synthesizing the lithium nickel oxygen material are weighed in proportion and added with deionized water, ground, washed and then spray-dried to obtain a dry powder of the lithium nickel oxygen material, the dry powder is sintered under a protective atmosphere, and cooled to obtain a lithium nickel oxygen positive electrode material.

[0038] In the present invention, for LiNi x Co y Mn 1-x-y The preparation method of O2 is not limited, and those skilled in the art can prepare the nickel-based positive electrode material according to conventional technical means. Exemplarily, a nickel-based positive electrode material precursor and a lithium source are mixed and sintered to obtain a nickel-based positive electrode material.

[0039] The nickel-based positive electrode material precursor may be one or more of an oxide, hydroxide and carbonate containing Ni, Co and Mn in a stoichiometric ratio, for example, a hydroxide containing Ni, Co and Mn in a stoichiometric ratio. The positive electrode active material precursor may be obtained by methods known in the art, for example, by coprecipitation, gel method or solid phase method.

[0040] As an example, a Ni source, a Co source and a Mn source are dispersed in a solvent to obtain a mixed solution; the mixed solution, a strong base solution and a complexing agent solution are simultaneously pumped into a stirred reactor in a continuous parallel flow reaction mode, the pH value of the reaction solution is controlled to be 10-13, the temperature in the reactor is 25°C-90°C, and an inert gas is passed during the reaction process; after the reaction is completed,

[0041] After aging, filtering, washing and vacuum drying, a hydroxide containing Ni, Co and Mn is obtained.

[0042] In some embodiments of the present invention, the Ni source includes at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate or nickel acetate; and / or the Co source includes at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate or cobalt acetate; and / or the Mn source includes at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate or manganese acetate; and / or the Li source includes at least one of lithium oxide (Li2O), lithium phosphate (Li3PO4), lithium dihydrogen phosphate (LiH2PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium carbonate (Li2CO3) or lithium nitrate (LiNO3).

[0043] The positive electrode active material precursor and the lithium source can be mixed by a ball mill mixer or a high-speed mixer. The mixed materials are added to an atmosphere sintering furnace for sintering. The sintering atmosphere is an oxygen-containing atmosphere, such as an air atmosphere or an oxygen atmosphere.

[0044] In addition, the nickel-based positive electrode material can also be coated. Specifically, the coating material is coated on the surface of the nickel-based positive electrode material by dry coating (high temperature solid phase method), and the surface of the nickel-based positive electrode material is partially or completely coated with a coating layer formed by the coating material. The coating layer contains at least one element selected from the following (hereinafter referred to as "coating element"): aluminum (Al), titanium (Ti), tungsten (W), boron (B), phosphorus (P), cobalt (Co), yttrium (Y) and silicon (Si).

[0045] Furthermore, the particle size of the nickel-based positive electrode material is 40-200 nm.

[0046] In the present invention, the positive electrode active material further comprises lithium iron manganese phosphate material, and the particle size of the lithium iron manganese phosphate material is 50-170 nm.

[0047] In the present invention, there is no particular limitation on the source of the lithium manganese iron phosphate material, which may be a commercially available product or may be prepared by a method known to those skilled in the art.

[0048] In the present invention, the preparation method of the lithium iron manganese phosphate material is not limited, and those skilled in the art can prepare the lithium iron manganese phosphate material according to conventional technical means. Exemplarily, the preparation method of the lithium iron manganese phosphate material includes the following steps:

[0049] Firstly, the lithium source, manganese source, iron source and phosphorus source required for synthesizing lithium manganese iron phosphate material are weighed in proportion and added with deionized water, and ground to obtain lithium manganese iron phosphate precursor slurry;

[0050] The carbon source is added to the lithium manganese iron phosphate precursor slurry and mixed evenly, and then ground, and then the solid content is adjusted and spray-dried to obtain a dry powder; the dry powder is sintered under a protective atmosphere, and the positive electrode active material is obtained after cooling.

[0051] In the present invention, the lithium source is selected from at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate and lithium acetate; the manganese source is selected from at least one of manganese carbonate, manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate and manganese acetate; the iron source is selected from at least one of ferrous oxalate, ferric hydroxide, ferrous hydroxide, ferric phosphate, ferrous phosphate, ferrous acetate, ferrous acetate, ferrous carbonate, ferrous carbonate, ferrous trioxide, ferric tetroxide and ferrous oxalate; the phosphorus source is selected from at least one of diammonium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate and lithium phosphate. The present invention preferably uses manganese iron phosphate as a manganese source, an iron source and a phosphorus source at the same time; or, preferably uses ferric phosphate as an iron source and a phosphorus source at the same time; the carbon source includes glucose.

[0052] The raw materials can be mixed by a ball mill mixer or a high-speed mixer. The mixed raw materials are dried to obtain a precursor.

[0053] The precursor is added into an atmosphere sintering furnace for sintering. The sintering atmosphere is an oxygen-containing atmosphere, such as an air atmosphere or an oxygen atmosphere.

[0054] In addition, the lithium iron manganese phosphate material can also be coated. Specifically, the coating material is coated on the surface of the lithium iron manganese phosphate material by dry coating (high temperature solid phase method), and the surface of the lithium iron manganese phosphate material is partially or completely coated with a coating layer formed by the coating material. The coating layer contains at least one element selected from the following (hereinafter referred to as "coating element"): aluminum (Al), titanium (Ti), tungsten (W), boron (B), phosphorus (P), cobalt (Co), yttrium (Y) and silicon (Si).

[0055] In the present invention, the molar ratio c of the nickel-based positive electrode material to the positive electrode active material can also affect the gas generation and performance of the battery.

[0056] The larger the c value, the more nickel-based materials are contained in the entire active material, and the less LMFP is contained. Although it can change the gas production path of the battery and reduce the production of hydrogen, the capacity of the battery is greatly reduced due to the small content of LMFP. The smaller the c value, the less nickel-based materials are contained in the entire active material, and the gas production of the entire electrode cannot be uniformly inhibited, resulting in excessive hydrogen production, which affects battery safety.

[0057] Therefore, the present invention can ensure the battery capacity and uniformly suppress the gas production of the entire electrode by controlling the c value range to 0.5%≤c≤40%.

[0058] In the present invention, the value range of c is 0.5%~40%, and can be 0.5%, 1%, 3%, 5%, 6%, 7%, 10%, 12%, 14%, 15%, 17%, 20%, 22%, 25%, 27%, 30%, 32%, 34%, 35%, 37%, 40%, and can be 0.5%~40%. In some preferred embodiments of the present invention, the value range of c is 5%~30%.

[0059] The test method of c is not limited in the present invention. Those skilled in the art can detect the molar ratio of the nickel-based positive electrode material to the positive electrode active material according to conventional technical means. Exemplarily, the test method of c includes the following steps:

[0060] At 25°C, the battery was discharged from 0.33C to 2.5V, and the battery was disassembled to obtain a positive electrode sheet and a negative electrode sheet. 2g of positive electrode powder was obtained from the positive electrode sheet, and 2g of negative electrode powder was obtained from the negative electrode sheet. The molar percentage of Ni and Mn elements in the positive electrode powder and the negative electrode powder was tested by inductively coupled plasma ICP. The element detection spectrum wavelength (Mn wavelength 257.61nm, Ni wavelength 232.0nm) was selected. According to the characteristics of the sample and the elements to be detected, appropriate ICP instrument working conditions were set, including a gas flow rate of 0.5L / min and a power of 1150W. The Mn and Ni contents of the elements were tested by ICP, and the molar percentage c of the nickel-based positive electrode material in the positive electrode active material was calculated according to the formula shown in Formula VI.

[0061] c=(total molar percentage of Ni in the positive electrode powder and the negative electrode powder / total molar percentage of nickel and manganese in the positive electrode powder and the negative electrode powder)×100% Formula VI

[0062] In the present invention, H + The growth rate b can also affect the gas production and performance of the battery.

[0063] H + The growth rate b represents the size of the active area of ​​the electrode, H + The larger the growth rate b is, the larger the active area of ​​the electrode is. + The smaller the growth rate b is, the smaller the active area of ​​the electrode is. + The growth rate b is related to factors such as the carbon coating degree, particle size, and distribution mode of the active material. A high b value indicates that the electrochemical reaction of the electrode is easier to proceed, or the reaction rate is faster. When the b value is too high, the reaction degree between the active material and the electrolyte is too high, which can easily cause too many side reactions, resulting in excessive gas production in the battery and black spots on the electrode. When the b value is too low, it means that the electrochemical reaction is difficult to proceed effectively, which may be due to the large particle size of the positive electrode active material particles and the large solid phase diffusion impedance caused by the excessively thick carbon layer, which makes the overall dynamics of the battery poor.

[0064] Therefore, in the present invention, it is necessary to control H + The range of growth rate b is 0.01≤b≤0.18, and can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, or any value between 0.01 and 0.18. In some preferred embodiments of the present invention, the value of b is 0.02≤b≤0.15.

[0065] By controlling the range of b to be 0.01≤b≤0.18, the present invention can ensure that the electrochemical reaction is effectively carried out while increasing the reaction rate as much as possible.

[0066] The present invention does not limit the testing method of H b. Those skilled in the art can use conventional technical means to test H b. + Growth rate was tested, for example, H + The test method for the growth rate b includes the following steps:

[0067] Two groups of positive electrodes of the same area of ​​the fully charged battery with the same SOC of 100% were immersed in the same volume of solution. One group of positive electrodes was stored at 60℃ for 48h, and the H + The content of H in the solution was measured at m1, in ppm. Another group of positive electrode sheets were stored at 60 °C for 72 h. + The content of m2, in ppm; H + The growth rate b is calculated according to the formula shown in formula III:

[0068] b=(m2-m1) / m1 Formula III;

[0069] The test area of ​​the positive electrode plate is 147 cm 2 ; Among them, the test area is 147cm 2 It can be the sum of the areas of the positive electrodes of multiple fully charged batteries. In some specific embodiments of the present invention, it can be 3 pieces of 7×7 cm 2 The positive electrode of a fully charged battery.

[0070] The solution is a mixed solution of ethylene carbonate EC, ethyl methyl carbonate EMC and lithium perchlorate. In the mixed solution, the concentration of lithium perchlorate is 1M, the volume ratio of ethylene carbonate EC to ethyl methyl carbonate EMC is 3:7, and the amount of the solution is 20 ml.

[0071] Specifically, the H + The test method for the content of includes the following steps:

[0072] Prepare 0.05 mol / L triethylamine titration solution by mixing triethylamine and EMC;

[0073] EC and EMC were mixed in a volume ratio of 3:7 to form a 20 mL mixed solution, and 2.13 g of lithium perchlorate was added to the mixed solution to obtain an immersion solution;

[0074] The test area is 147cm 2 The positive electrode of the fully charged battery is mixed with the soaking solution and soaked at 60°C for 48 hours to obtain a 48-hour positive electrode soaking solution; 10 to 30 drops of methyl red are added to the 48-hour positive electrode soaking solution as an indicator, and triethylamine titration solution is dripped into the 48-hour positive electrode soaking solution containing methyl red, and the amount of triethylamine titration solution V1 when the 48-hour positive electrode soaking solution turns orange is recorded, and the H in the solution stored for 48 hours is calculated according to formula IV. + Content m1;

[0075] m1=M×V1×20010 / m Formula IV

[0076] In formula IV, M is the concentration of the titrant, in mol / L;

[0077] V1 is the volume of the consumed titrant, in mL;

[0078] m is the mass of the immersion liquid, in g;

[0079] Similarly, the H + The test method for the content of includes the following steps:

[0080] Prepare 0.05 mol / L triethylamine titration solution by mixing triethylamine and EMC;

[0081] EC and EMC were mixed in a volume ratio of 3:7 to form a 20 mL mixed solution, and 2.13 g of lithium perchlorate was added to the mixed solution to obtain an immersion solution;

[0082] The test area is 147cm 2 The positive electrode of the fully charged battery is mixed with the soaking solution and soaked at 60°C for 72 hours to obtain the 72-hour positive electrode soaking solution; 10 to 30 drops of methyl red are added to the 72-hour positive electrode soaking solution as an indicator, and triethylamine titration solution is dripped into the 72-hour positive electrode soaking solution containing methyl red, and the amount of triethylamine titration solution V2 when the 72-hour positive electrode soaking solution turns orange is recorded, and the H2 in the 72-hour solution is calculated according to the formula V. + Content m2;

[0083] m1=M×V2×20010 / m Formula V

[0084] In formula IV, M is the concentration of the titrant, in mol / L;

[0085] V2 is the volume of the consumed titrant, in mL;

[0086] m is the mass of the immersion liquid in g.

[0087] Substitute the above-obtained m1 and m2 into formula III to calculate H + The growth rate b.

[0088] In the present invention, the values ​​of a and b are measured when the battery is at 100% SOC, and c is measured when the battery is at 0% SOC. In the present invention, the battery is defined as 0% SOC when it is discharged from 0.33C to 2.5V at 25°C.

[0089] In the formula shown in Formula I, a×c can reflect to a certain extent the content of trivalent nickel element and tetravalent nickel element in the positive electrode material in the entire positive electrode active material. The larger the value of a×c, the higher the content of trivalent nickel element and tetravalent nickel element, and the smaller the value of a×c, the lower the content of trivalent nickel element and tetravalent nickel element in the entire positive electrode active material.

[0090] In the present invention, the value range of a×c is controlled to meet the range of 0.001≤a×c≤0.092. When the value of a×c is lower than 0.01, it means that the content of trivalent nickel and tetravalent nickel in the pole piece is low, resulting in the nickel-containing material adding to the pole piece. The improvement performance of the nickel-containing material on the gas production path is reduced, that is, the performance of the nickel-containing material in inhibiting hydrogen production is reduced. When the value of a×c is higher than 2.6, it means that the content of trivalent nickel and tetravalent nickel in the pole piece is too much. Affecting the content of lithium iron manganese phosphate in the positive electrode material, thereby reducing the capacity of the battery cell and the energy density of the battery.

[0091] Therefore, the present invention controls the value range of a×c to satisfy the range of 0.001≤a×c≤0.092, so that the nickel-containing material can have a good performance of changing the gas production path of the battery, that is, reducing the output of hydrogen, while ensuring a good energy density of the battery.

[0092] In the present invention, the 0.001≤a×c≤0.092 may be 0.001, 0.002, 0.003, 0.004, 0.005, 0.007, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.092, or any value between 0.001 and 0.092. In some preferred embodiments of the present invention, 0.003≤a×c≤0.06.

[0093] In the present invention, the battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.

[0094] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. In addition to the above-mentioned positive electrode active material, the positive electrode active material layer may also contain a conductive agent and a binder.

[0095] The conductive agent is used to provide conductivity in the electrode. Any conductive agent can be used without particular limitation as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Preferred are carbon materials such as carbon nanofibers, carbon blacks such as acetylene black and Ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, and carbon nanotubes.

[0096] The binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Therefore, in the embodiment, the binder suitable for use is a fluorinated polyolefin binder, which may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (e.g., carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.

[0097] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.

[0098] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art. For example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent, and the solvent can be N-methylpyrrolidone (NMP) or deionized water to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the positive electrode current collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.

[0099] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material and may further comprise a conductive agent and / or a binder.

[0100] The present invention has no particular limitation on the negative electrode current collector as long as it has high conductivity without causing adverse chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or an aluminum-cadmium alloy can be used.

[0101] For the negative electrode active material, the embodiments of the present invention do not specifically limit the type of the negative electrode active material, and it can be selected according to actual needs. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO m (0 < m < 2, such as m = 1), lithium titanate Li4Ti5O with a spinel structure 12 or one or more of them.

[0102] The embodiments of the present invention do not specifically limit the types of the conductive agent and the binder in the negative electrode active material layer, and they can be selected according to actual needs. As an example, the conductive agent is one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder is one or more of styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, water-based acrylic resin, and carboxymethyl cellulose. The negative electrode active material layer may also optionally include a thickener, such as carboxymethyl cellulose.

[0103] The electrolyte of the present invention can be various electrolytes applicable to electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte usually includes a lithium salt.

[0104] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluoro(oxalato)borate (LiDFOB), lithium bis(oxalato)borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluoro(dioxalato)phosphate (LiDFOP), and lithium tetrafluoro(oxalato)phosphate (LiTFOP). The concentration of the electrolyte in the electrolyte can be 0.5 - 5 mol / L.

[0105] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE). Based on the weight of the electrolyte, the weight content of the solvent can be 70-98%.

[0106] In addition, the electrolyte may further include additives. Specifically, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0107] The electrochemical device may further include a diaphragm, which is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm may be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.

[0108] An embodiment of the present invention provides an electronic device, comprising the battery described above. The electrochemical device serves as a power supply for the electronic device.

[0109] The electronic device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0110] In order to further understand the present invention, the battery provided by the present invention is described below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0111] Example 1

[0112] 1) Preparation of LMFP cathode materials:

[0113] According to LiMn 0.6 Fe 0.4 The molar ratio of each element Li, Mn, Fe, and P in the PO4 chemical formula is 1 mol lithium carbonate, 0.6 mol manganese carbonate, 0.4 mol ferrous oxalate, and 1 mol diammonium hydrogen phosphate. Deionized water is added, mixed, and ball milled to obtain lithium iron manganese phosphate precursor slurry. Then 30% glucose is weighed and mixed evenly with the lithium iron manganese phosphate precursor slurry, ball milled for 20 hours, and then the solid content is adjusted and spray dried to obtain dry powder; after preliminary filtration, the precursor can be obtained. Then the precursor is placed in a tubular furnace for calcination, and the heating rate is 5℃ / min to 600℃ for pre-calcination for 300min, and then the temperature is increased to 800℃ at a heating rate of 10℃ / min, calcined for 720min, and naturally cooled to obtain LiMn 0.6 Fe 0.4 PO4 aggregates. Then LiMn 0.6 Fe 0.4 The PO4 aggregates were crushed and ground, and after 8 hours of crushing, LiMn was screened. 0.6 Fe 0.4 PO4 positive electrode material.

[0114] 2) Preparation of positive electrode: Lithium iron manganese phosphate (LiMn 0.6 Fe 0.4 PO4) and nickel-based positive electrode material lithium nickel oxide (LNO) positive electrode material are mixed evenly in a molar ratio of 17.01:3.79 as the main material. The main material and the conductive agent SP and PVDF glue are mixed evenly in NMP in a mass ratio of 96.5:1.5:2. Then, the mixed positive electrode slurry is mixed at a surface density of 400g / m 2 The positive electrode sheet is uniformly coated on the aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then cut into strips; the positive electrode sheet is uniformly coated on the aluminum foil, dried in a vacuum oven at 100°C to obtain the positive electrode sheet, and then cut into strips; then roll-pressed and cut to obtain the positive electrode sheet.

[0115] 3) Preparation of negative electrode sheet: artificial graphite, conductive agent SP, and PVDF glue system were evenly mixed in a mass ratio of 96.4:0.6:3, dispersed in deionized water to obtain negative electrode slurry, and the negative electrode slurry was prepared at a surface density of 173g / m 2 Evenly coated on copper foil, dried at 100℃ in vacuum environment for 12h, then cut into strips and heated to 1.65g / cm 3 The compaction density is cold pressed to obtain the negative electrode sheet.

[0116] 4) Preparation of electrolyte: The electrolyte has EC:EMC=3:7 wt% as solvent system, 1.15M LiPF6 as lithium salt, and 1% VC (vinylene carbonate) and 1% MMDS (methylene disulfonate) as film-forming additives.

[0117] 5) Preparation of isolation film: Select PP as the isolation film.

[0118] 6) Assemble the battery, form, and constant capacity to form SEI / CEI: Stack the above-mentioned positive electrode sheet, isolation film, and negative electrode sheet in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging shell, inject electrolyte after drying, and the injection coefficient is formed through 0.02C to 3.5V / 0.1C to 4.25V formation, and form a stable SEI on the negative electrode side. The second seal extracts more gas, charges at 0.33C to the upper limit voltage, and charges at a constant voltage of 0.05C and cuts off, and discharges at 0.33C to the lower limit voltage of 2.5V, and charges and discharges twice to form a stable CEI on the positive electrode side.

[0119] Examples 2 to 18 and Comparative Examples 1 to 4

[0120] Examples 2 to 18 and Comparative Examples 1 to 4 provide a lithium-ion battery, respectively. The preparation method is similar to that of Example 1, except that when preparing the positive electrode sheet, the type of nickel-based positive electrode material and lithium iron manganese phosphate (LiMn 0.6 Fe 0.4 The ratio of PO4) and nickel-based positive electrode materials is shown in Table 1.

[0121] For the batteries prepared in each embodiment and comparative example, the testing methods of various parameters are as follows:

[0122] ①The specific test method of a value is as follows:

[0123] The positive electrode sheet was disassembled when the battery was in a fully charged state of 100% SOC, and the positive electrode sheet was cleaned with DMC (dimethyl carbonate), and then dried at 25°C for 24 hours to obtain a treated positive electrode sheet;

[0124] After the positive electrode sheet is processed, it is etched by X-ray photoelectron spectroscopy (XPS) method. The instrument specification model is NEXSA G2. The test beam is set to 400 microns in the manual control window of the instrument. According to the element to be tested, the instrument automatically supplements the test energy range, the etching dwell time is 50ms, the step length is 1eV, the rate is 0.7nm / s, and the etching time is set to 60s. After the test, the instrument will automatically give the test results and fit the peak area of ​​each valence state according to the binding energy.

[0125] a is calculated according to the formula shown in formula II:

[0126] a=(S Ni 4+ +S Ni 3+ ) / S 总面积 Formula II;

[0127] In formula II, S Ni 4+ represents the area of ​​tetravalent nickel obtained by XPS test;

[0128] S Ni 3+ represents the area of ​​trivalent nickel obtained by XPS test;

[0129] S 总面积 It indicates the sum of the peak areas of each valence state of nickel element obtained by XPS test.

[0130] The calculated a values ​​are shown in Table 1.

[0131] ②The test method of b value is as follows:

[0132] The positive electrode of the battery in a fully charged state of 100% SOC was immersed in the solution and stored at 60°C for 48 hours. The H + The content of H in the solution was measured at 60 °C for 72 h. + The content of m2, in ppm, H + The growth rate b is calculated according to the formula shown in formula III:

[0133] b=(m2-m1) / m1 Formula III;

[0134] The test area of ​​the positive electrode plate is 147 cm 2 , specifically 3 pieces of 7×7cm 2 The positive electrode of a fully charged battery;

[0135] The solution is a mixed solution of ethylene carbonate EC, ethyl methyl carbonate EMC and lithium perchlorate. In the mixed solution, the concentration of lithium perchlorate is 1M, the volume ratio of ethylene carbonate EC to ethyl methyl carbonate EMC is 3:7, and the amount of the solution is 20 ml.

[0136] Storage 48h solution H + The test method for the content of includes the following steps:

[0137] Prepare 0.05 mol / L triethylamine titration solution by mixing triethylamine and EMC;

[0138] EC and EMC were mixed in a volume ratio of 3:7 to form a 20 mL mixed solution, and 2.13 g of lithium perchlorate was added to the mixed solution to obtain an immersion solution;

[0139] 3 pieces of 7×7cm 2 The positive electrode of the fully charged battery is mixed with the soaking solution and soaked at 60°C for 48 hours to obtain a 48-hour positive electrode soaking solution; 10 to 30 drops of methyl red are added to the 48-hour positive electrode soaking solution as an indicator, and triethylamine titration solution is dripped into the 48-hour positive electrode soaking solution containing methyl red, and the amount of triethylamine titration solution V1 when the 48-hour positive electrode soaking solution turns orange is recorded, and the H in the solution stored for 48 hours is calculated according to formula IV. + Content m1;

[0140] m1=M×V1×20010 / m Formula IV

[0141] In formula IV, M is the concentration of the titrant, in mol / L;

[0142] V1 is the volume of the consumed titrant, in mL;

[0143] m is the mass of the immersion liquid, in g;

[0144] Similarly, the H + The test method for the content of includes the following steps:

[0145] Prepare 0.05 mol / L triethylamine titration solution by mixing triethylamine and EMC;

[0146] EC and EMC were mixed in a volume ratio of 3:7 to form a 20 mL mixed solution, and 2.13 g of lithium perchlorate was added to the mixed solution to obtain an immersion solution;

[0147] 3 pieces of 7×7cm 2 The positive electrode of the fully charged battery is mixed with the soaking solution and soaked at 60°C for 72 hours to obtain the 72-hour positive electrode soaking solution; 10 to 30 drops of methyl red are added to the 72-hour positive electrode soaking solution as an indicator, and triethylamine titration solution is dripped into the 72-hour positive electrode soaking solution containing methyl red, and the amount of triethylamine titration solution V2 when the 72-hour positive electrode soaking solution turns orange is recorded, and the H2 in the 72-hour solution is calculated according to the formula V. + Content m2;

[0148] m2=M×V2×20010 / m Formula V

[0149] In formula IV, M is the concentration of the titrant, in mol / L;

[0150] V2 is the volume of the consumed titrant, in mL;

[0151] m is the mass of the immersion liquid in g.

[0152] Substitute the above-obtained m1 and m2 into formula III to calculate H + The growth rate b.

[0153] ③The test method of c value is as follows:

[0154] At 25°C, the battery was discharged from 0.33C to 2.5V, and the battery was disassembled to obtain the positive electrode sheet and the negative electrode sheet. 2g of positive electrode powder was obtained from the positive electrode sheet, and 2g of negative electrode powder was obtained from the negative electrode sheet. The molar percentage of Ni and Mn elements in the positive electrode powder and the negative electrode powder was tested by inductively coupled plasma ICP, and the molar percentage c of the nickel-based positive electrode material in the positive electrode active material was calculated according to the formula shown in Formula VI.

[0155] c=(total molar percentage of Ni in the positive electrode powder and the negative electrode powder / total molar percentage of nickel and manganese in the positive electrode powder and the negative electrode powder)×100% Formula VI

[0156] The lithium-ion batteries prepared in the above embodiments and comparative examples were subjected to performance tests, and the specific items and methods are as follows:

[0157] ① Normal temperature cycle test method:

[0158] At 45°C, charge at 0.33C to 4.3V, discharge at 0.33C to 2.5V. After two cycles of constant capacity, charge at 45°C with 1C constant current and constant voltage to 4.3V, discharge at 1C constant current to 2.5V. After repeating the cycle 200 times, record the discharge capacity at the 3rd cycle as C1, and the discharge capacity at the 200th cycle as C2. The capacity retention rate of 200 cycles = (C2 / C1) × 100%.

[0159] ②DCR growth rate test method:

[0160] At a temperature of 45°C, charge to 4.3V at 0.33C, discharge to 2.5V at 0.33C, and set the capacity for two cycles; at a temperature of 45°C, charge to 4.3V at 0.33C constant current and constant voltage, then discharge to 80% SOC at 0.33C, let stand for two hours, discharge at 1C for 18S and measure 1CDCR as R0; discharge the battery to 2.5V at 45°C at 0.33C; and continue to charge the battery to 4.3V at 1C constant current and constant voltage at 45°C, discharge to 2.5V at 1C constant current, repeat the 1C / 1C charge and discharge cycle for 200 cycles; charge to 4.3V at 0.33C at 45°C again, discharge to 2.5V at 0.33C, set the capacity for two cycles, discharge the battery to 80% SOC at 0.33C, let stand for two hours, discharge at 1C for 18S and measure 1C DCR is denoted as R1, and the DCR growth rate for 200 cycles = [(R1-R0) / R0]×100%.

[0161] The test results are shown in Table 1.

[0162] Table 1

[0163]

[0164] For the lithium-ion batteries prepared in various embodiments of the present invention, the 200cls cycle capacity retention rate is ≥91.81%, and the DCR growth rate is ≤10.25%. It can be seen that the gas production of the lithium-ion battery of the present invention is reduced, thereby reducing the internal resistance of the battery and improving the cycle performance of the battery.

[0165] It can be seen from the data of Examples 1 to 5 and Examples 10 to 11 combined with Examples 6 to 9, Examples 12 to 18 and Comparative Examples 1 to 4 that when a, b, c and a×c meet the preferred parameter range defined by the present invention, the internal resistance of the lithium-ion battery is lower and the cycle performance is relatively better.

[0166] From Examples 1 to 5 in combination with Examples 6 to 9, it can be seen that when the battery satisfies 0.008<(a×c) / b≤8.290, the internal resistance of the lithium-ion battery is lower and the cycle performance is relatively higher.

[0167] It can be seen from the results of Comparative Examples 1 to 4 that even when a, b, c and a×c meet the parameter range defined by the present invention, when the battery does not meet the range of 0.008<(a×c) / b≤8.290, the lithium-ion battery has a higher internal resistance and poorer cycle performance.

[0168] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A battery, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material, wherein the positive electrode active material comprises a lithium iron manganese phosphate material and a nickel-based positive electrode material, wherein the nickel-based positive electrode material comprises a trivalent nickel element and a tetravalent nickel element, wherein the nickel-based positive electrode material is selected from a nickel-containing ternary positive electrode material, wherein the nickel-containing ternary positive electrode material is selected from a nickel-cobalt-manganese ternary positive electrode material, wherein the nickel-cobalt-manganese ternary material is LiNi x Co y Mn 1-x-y O2, where 0.9<x<1, 0<y<0.1; The molar ratio of the nickel-based positive electrode material to the positive electrode active material is c; when the battery is in a state of 100% SOC, the percentage of the total molar amount of the trivalent nickel element and the tetravalent nickel element to the total molar amount of the nickel element in the nickel-based positive electrode material is a; the H + The growth rate is b, and a, c and b satisfy the relationship shown in Formula I: 0.025<(a×c) / b≤2.860, formula I.

2. The battery according to claim 1, characterized in that 0.3%≤a≤23%。 3. The battery according to claim 1, characterized in that 1%≤a≤20%。 4. The battery according to claim 1, characterized in that 0.01≤b≤0.18。 5. The battery according to claim 1, characterized in that 0.02≤b≤0.15。 6. The battery according to claim 1, characterized in that 0.5%≤c≤40%。 7. The battery according to claim 1, characterized in that 5%≤c≤30%。 8. The battery according to claim 1, characterized in that 0.001≤a×c≤0.

092.

9. The battery according to claim 1, characterized in that 0.003≤a×c≤0.

06.

10. The battery according to claim 1, characterized in that The molar ratio of the trivalent nickel element to the tetravalent nickel element is 1:10 to 6:

10.

11. The battery according to claim 1, characterized in that The battery also includes a negative electrode plate, a separator and an electrolyte; The negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material is selected from natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon, silicon-carbon composite, SiO m , 0 <m<2、Li4Ti5O 12 One or more of; The separator is selected from one of PP, PE, and PP / PF; The electrolyte comprises a lithium salt and a solvent, wherein the lithium salt is selected from a combination of one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluorooxalate phosphate or lithium bis(oxalatoborate), and the solvent is selected from a combination of one or more of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate or dimethyl carbonate.

Citation Information

Patent Citations

  • Application of additive, electrode slurry, additive slurry, lithium ion battery positive electrode or negative electrode and preparation method therefor, and lithium ion battery

    CN106601991A

  • Lithium ion battery

    CN115882043A

  • High-nickel ternary positive electrode material for lithium battery, preparation method of high-nickel ternary positive electrode material and lithium battery

    CN116230882A

  • Positive electrode material, positive plate containing positive electrode material and lithium ion battery

    CN116454228A

Cited By

  • Battery

    WO2026091415A1